Collaborative Governance in Local Policy Implementation: A Case Study of Flood Risk Management in South Jakarta - Sanyoto, Yahnu Wiguno; Hutauruk, Rosinta Paulina; Sa’adih, Sa’adih (JURNAL SOSIAL DAN HUMANIS SAINS, 2021)
This study explores the practice of collaborative governance in local policy implementation, focusing on flood risk management in South Jakarta. The increasing complexity of urban environmental issues necessitates multi-stakeholder collaboration that transcends traditional bureaucratic boundaries. Using a qualitative approach, this research analyzes how government agencies, communities, NGOs, and the private sector interact and share responsibilities in managing urban floods. Findings suggest that trust-building, leadership, and institutional arrangements are critical to successful collaboration, although challenges remain in coordination and resource alignment. Recommendations are offered to enhance collaborative governance practices in urban resilience policies.